An audit and analysis of cancer patients attending radiation oncology department: a tertiary care center experience - Das, Bishnu Prasad; Patra, Jitendra (International Journal Of Community Medicine And Public Health, 2020)
Background: Cancer is a major public health problem worldwide and is the second leading cause of death in the developing countries. Among various diseases, cancer has become a big threat to human beings globally. As per Indian population census data, the rate of mortality due to cancer in India was high and alarming with about 8,06,000 existing cases by the end of the last century. In view of these facts, the present article describes the status of various types of cancers in the southern part of Odisha. Methods: A total of 1123 patients were registered in the department of radiotherapy, maharaja krushna chandra gajapati medical college, Odisha, during the period from January to December 2019 and were included for the retrospective analysis. Results: Females outnumbered males with a ratio of 1.32. Highest number of the patients belong to the age group of 60-69 years. Major cancer sites in females were cervix, breast followed by head and neck. Leading cancer sites in males were head and neck, stomach, rectum and lungs. Most of the cases presented in advanced stage of disease (78%). Squamous cell carcinoma was the most common histopathology (81%). A significant proportion of patients defaulted after undergoing preliminary investigations (27.4%). Out of the total (1123) population 482 patients received radiation and 760 patients received chemotherapy and 425 received supportive care. Conclusions: The outcome of this study will significantly help us to understand the cancer burden in southern Odisha and its distribution to define region specific strategies for cancer management.